(3ZGjI CeGfj GdWGdH aj TQM cGajI GHf GdMGLHs - (3fLe GdOjf CMeO Hf eMeO Hf CHj GdMRe GdbQTj GdeNRhej Gdbehdjs; (3YKeGf Hf YeQ Hf CHj HcQ Hf jhfS, CHh YeQh LeGd GdOjf GHf GdMGLH,J (B646 (3g` s
(3ChdgG (B:s
(3bGd(B: (3hcde GdeLGRGI JONd Ydi aYdjf GYGde Cf cde GdeLGRGI GdeJbOe PcQgG JONd Ydi LedJjf s
(3BNQgG (B:s
(3hEf cGf eG bHdgG eaJhMkG obdHJ CdakG afbhd aj GVQHf RjOkG VQHkG, Je GdcJGH s
(3GdLRA GdChd ef gPg GdfSNI ehLhO aj GdeJMa GdHQjWGfjs
(3bdjd GdfbWs
(3HChdgG hba HGdbGgQI eDQN aj (B828(3g``s
(3JHUQI GdYfhGf (B:s
(3TQMs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdfMhs